2006
DOI: 10.1007/s00464-005-0474-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pancreaticoduodenectomy for benign and malignant diseases

Abstract: Laparoscopic pancreatoduodenectomy for selected cases of benign and malignant lesions performed by highly skilled laparoscopic surgeons is feasible and safe. This method can obtain adequate margins and follow oncological principles. Larger series and longer follow-up periods are needed to establish the current results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 24 publications
(21 reference statements)
5
113
0
10
Order By: Relevance
“…Despite the known benefits of laparoscopy, the anatomic challenges, the inherent technical complexity of this operation and the difficulty of performing three major anastomoses have limited the widespread use of minimally invasive cal and reconstructive challenges previously mentioned. There are two general approaches to MIPD: a total laparoscopic approach (TLPD) where the anastomoses (pancreaticojejunostomy, hepaticojejunostomy, gastrojejunostomy) along with the resection are done intracorporeally; and the laparoscopic-assisted, or hybrid approach where the reconstruction is done through a small incision which is also used for specimen extraction [38,40,42,[44][45][46] .…”
Section: Minimally Invasive Pancreaticoduodenectomymentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the known benefits of laparoscopy, the anatomic challenges, the inherent technical complexity of this operation and the difficulty of performing three major anastomoses have limited the widespread use of minimally invasive cal and reconstructive challenges previously mentioned. There are two general approaches to MIPD: a total laparoscopic approach (TLPD) where the anastomoses (pancreaticojejunostomy, hepaticojejunostomy, gastrojejunostomy) along with the resection are done intracorporeally; and the laparoscopic-assisted, or hybrid approach where the reconstruction is done through a small incision which is also used for specimen extraction [38,40,42,[44][45][46] .…”
Section: Minimally Invasive Pancreaticoduodenectomymentioning
confidence: 99%
“…Most MIPD series report low mortality rate [38][39][40][41][42][43][44][45][46] ; Gumbs et al [48] reviewed 285 cases and found the overall mortality was 2%. A more recent series reports a 100-d mortality rate of 5.7%, which is not significantly different than the mortality rate of 8.8% in the OPD group in the same series [35] .…”
Section: Post-operative Recoverymentioning
confidence: 99%
See 3 more Smart Citations